1967
DOI: 10.6028/jres.071c.024
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced acoustic cavitation; apparatus and some results

Abstract: Equipment and techniques for acoustic cavitation w o~k are desc ribed . . The tes t liquid and its eontainer form part of a se lf· sustaining programmable oscIllator. EmphasIs IS laId on the treatme nt of the liquid necessa ry to yield re producible res ults after artificial nucl ea tion ,. especially b y ne utrons , a-recoi ls, and fi ss ion. With ne utrons , for instance, th e ca vitatIOn rate rI ses rapI~ly WIth acoustIc (negativ e) press ure, and at fix ed pressure is proportional to ne utron flux . The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 3 publications
8
76
1
Order By: Relevance
“…Greenspan & Tschiegg [20] filtered away motes from distilled water and found that the tensile strength of water, measured by acoustic cavitation at 43 kHz, increased as the size of the motes became smaller, until at 0.2 mm a tensile strength of more than 200 bar could be sustained for seconds. Likewise, the tensile strength was increased when the gas content in the water was reduced, but when filtered to mote sizes smaller than 0.2 mm the gas content did not affect the tensile strength.…”
Section: Tensile Strength Of Particlesmentioning
confidence: 99%
“…Greenspan & Tschiegg [20] filtered away motes from distilled water and found that the tensile strength of water, measured by acoustic cavitation at 43 kHz, increased as the size of the motes became smaller, until at 0.2 mm a tensile strength of more than 200 bar could be sustained for seconds. Likewise, the tensile strength was increased when the gas content in the water was reduced, but when filtered to mote sizes smaller than 0.2 mm the gas content did not affect the tensile strength.…”
Section: Tensile Strength Of Particlesmentioning
confidence: 99%
“…This may explain the very high tensile strength, its lack of dependency on particle size ͑when smaller than 0.2 m͒, as well as the lack of dependency on the gas content observed by Greenspan and Tschiegg. 12 The acoustic field they used to generate tensile stress has probably caused rectified diffusion of gas into small nano-voids, and this has made them grow over time, and has limited the duration of the high tensile strength. Significant contamination of the particle surfaces with amphiphilic surface-active substances is probably required for the tensile strength to reduce to that of skin-covered vapor bubbles of equivalent size.…”
Section: -3mentioning
confidence: 99%
“…Fluids 19, 072104 ͑2007͒ cleaned 7,10 or just distilled, and motes larger than 0.2 m are removed. 12 However, it is well known that clean surfaces contaminate very quickly when exposed to the environment, and generally surface-active molecules can be expected to form a skin around particles in water.…”
Section: -5mentioning
confidence: 99%
“…The discussion of their nature -stabilized spherical gas bubbles or surface nuclei on particles -has been ongoing. Though [3,5,8,9] point to the latter ones, the direct observation of cavity-particle separation has been missing until now. Further, the particle ejection suggests that accelerated particles may penetrate into nearby soft surfaces, e.g., biological tissue or cells during exposure to strong, focused sound fields.…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Ending 30 Aprmentioning
confidence: 99%